Analisis Pengaruh Variabel Ekonomi Makro Terhadap Volatilitas Indeks Saham Syariah Indonesia (ISSI) - Nanang Widyantoro; Rifki Ismal; Hendri Tanjung (Indonesian Journal of Islamic Economics and Business, 2023)
This study aims to analyze the impact of the movement of the main macroeconomic indicators on ISSI volatility. Then analyzed how far the influence of ISSI volatility on investors' decisions in investing in ISSI shares. Furthermore, policy proposals can be made to control the impact of the main macroeconomic indicators on ISSI volatility. This study uses the VAR (Vector Autoregression) / VECM (Vector Error Correction Model) method with a sample of 130 (one hundred and thirty) monthly time series data from June 2011 to March 2022. The results of the analysis and findings in this study can provide information that the variables macroeconomics namely Inflation, World Oil Prices, Exchange Rates, Money Supply and Trade Transaction Volume variables significantly influence ISSI volatility. The positive relationship between ISSI Volatility and ISSI Trading Transaction Volume indicates that ISSI Volatility influences investors' decisions to invest in ISSI shares. So that policy priorities are needed in order to control stock volatility, including controlling inflation, world oil prices, exchange rates and the money supply. Control over the volume of trade transactions also needs to be done to reduce investment risk.